Citometria de fluxo e anatomia caulinar como indicadores de compatibilidade de mudas cítricas - Nascimento, Paula Almeida (2017)
Effective grafting is a consequence of the canopy's compatibility with the rootstock, that is, a successful combination between two distinct plant parts that continues to grow into a single individual. In the citriculture, there is a need for diversification of the use of rootstocks, as it is extremely important to know the behavior of the crown-x citric rootstock combinations. It is known that the rootstock influences the canopy variety in a series of characteristics that will determine its greater or lesser productive capacity. Thus, in order to observe the possibility of occurrence of early incompatibility and the rootstock influence on the DNA content between orange and mandarin crown varieties in different citrus rootstocks, flow cytometry analysis and anatomy of grafting area were performed . Two graft and rootstock compatibility experiments were carried out: one with orange cultivars with the varieties 'Lane Late', 'Navelate ', 'Navelina' and another experiment with the mandarins with the 'Clemenules' and 'Okitsu' Satsuma and the 'Ortanique' hybrid. The crowns of orange and mandarin were grafted on five rootstocks of different citrus varieties: ' St. Cruz Clave Lemon Tree, ' Tropical Sunki ' Mandarin Tree, 'Índio' Citrandarin, 'San Diego' Citrandarin, 'Swingle' Citrumelo. Flow cytometry analyzes were performed using a Completely Randomized Design, CRD, in a factorial scheme with 3 (crowns) x 5 (rootstock), with three replications. The DNA contents of the leaves and roots of each combination of oranges and mandarins crowns on the various citrus rootstocks were evaluated. Statistical differences were found in the DNA contents of the leaves; however, the DNA contents of the roots were not significant. While, in the analysis of the seedlings wood anatomy, transversal and longitudinal anatomical sections of the sections of the stems were evaluated in the area of the grafting. The design was Completely Randomized, CRD, in a 2 x 4 factorial scheme, the first factor being the two 'Navelina' and 'Clemenules' crown cultivars and the second factor the four rootstocks: 'Índio' and 'San Diego' Citrandarins, Clave Lemon Tree 'Sta. Cruz' and 'Sunki Tropical' Mandar in. Thus, statistical analyzes were performed by measuring the rays heights rays with n = 30 repetitions and the vessel diameters measurement with n = 40 repetitions. Statistical differences were found in the rays heights and vessel diameters average of the evaluated treatments. The conclusion is that orange and mandarin canopy varieties tend to vary the DNA content according to the rootstock used. In the histological sections of the crowns x rootstock analyzed combinations of the wood, after one year of gr afting, they presented formation and the proliferation of disorganized cells (callus), observing some connection of the vascular elements between graft and rootstock.